2017
DOI: 10.3168/jds.2017-12616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of corn grain with lactose in calf starters on ruminal fermentation and growth performance

Abstract: The objective of this study was to evaluate effects of partial replacement of dry ground corn with lactose in calf starters on dry matter intake, growth rate, ruminal pH, and volatile fatty acid profile. Sixty Holstein bull calves were raised on a high plane of nutrition program until 55 d of age. Calves were fed texturized calf starters containing 30.1% steam-flaked grains and lactose at 0 (control), 5, or 10% (n = 20 for each treatment) on a dry matter basis. All calves were fed treatment calf starters ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
4
2
Order By: Relevance
“…The starter and kleingrass DMI gradually increased from the beginning of the study and rapidly increased from 5 weeks after birth as weaning approached in both treatments (Time p < 0.01; Figure b,c), this is because the amount of MR fed was maximum from 3 to 6 weeks after birth and decreased thereafter (Time p < 0.01; Figure a). In our previous study, starter and hay DMI were higher in weaning transition period (42 to 55 days after birth) than in pre‐weaning period (7 to 41 days after birth) in calves fed MR according to the same feeding strategy as the current study (Saegusa et al, ), consistent with the present study. No effects of treatment and treatment by time interaction were observed for kleingrass DMI.…”
Section: Resultssupporting
confidence: 92%
“…The starter and kleingrass DMI gradually increased from the beginning of the study and rapidly increased from 5 weeks after birth as weaning approached in both treatments (Time p < 0.01; Figure b,c), this is because the amount of MR fed was maximum from 3 to 6 weeks after birth and decreased thereafter (Time p < 0.01; Figure a). In our previous study, starter and hay DMI were higher in weaning transition period (42 to 55 days after birth) than in pre‐weaning period (7 to 41 days after birth) in calves fed MR according to the same feeding strategy as the current study (Saegusa et al, ), consistent with the present study. No effects of treatment and treatment by time interaction were observed for kleingrass DMI.…”
Section: Resultssupporting
confidence: 92%
“…However, relative to the baseline (1 wk of age; Figure 4A), the plasma GLP-1 concentration was higher (P < 0.01) for the LAC10 (126.8 ± 6.34%) than for the LAC5 (68.5 ± 6.35%) and for the control (36.3 ± 6.06%), and for the LAC5 than for the control. In the present study, no difference was observed in starter and hay intake across the 3 treatment groups (Saegusa et al, 2017), indicating that higher relative values of GLP-1 concentration observed for LAC5 and LAC10 are likely attributed to lactose inclusion in calf starters. However, as we did not measure nutrient composition of orts, we cannot exclude a possibility that pellet containing lactose was sorted, and it should be noted that extent of sorting could affect results of the present study.…”
Section: Glp-1contrasting
confidence: 62%
“…The procedures used in the present study were performed in accordance with principles and guidelines for animal use set by Hiroshima University, and all experimental procedures were approved by the Animal Care and Use Committee of Hiroshima University. The detailed procedure was described in a companion paper (Saegusa et al, 2017). Forty-five Holstein bull calves, BW of 46.7 ± 0.7 kg and 5.0 ± 0.1 d of age (mean ± SE), were born on March 20 to April 13, 2015 (n = 21) and May 7 to June 2, 2015 (n = 24).…”
Section: Animals and Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple sugars such as glucose or lactose increase butyrate production in the rumen without a significant effect on rumen pH (Chamberlain et al, 1993). However, Saegusa et al (2017) fed texturized CS containing 0, 5, or 10% lactose and reported no effect on ruminal butyrate concentrations, though increasing lactose increased molar proportion of acetate and minimum ruminal pH. Others have reported that replacing starch with sugars (e.g., molasses or glucose) increased growth (Atai and Harshbarger, 1965), increased plasma BHB , or altered rumen fermentation (Oltramari et al, 2016).…”
Section: Effect Of Carbohydrate Source On Ttdmentioning
confidence: 99%